VALUASI EKONOMI DEGRADASI DALAM MEWUJUDKAN KOTA HIJAU DI JAKARTA - Edi Wahyu Wibowo; Darwati Susilastuti; Meirinaldi Meirinaldi (Gapenas Publisher, 2022)
Sustainable urban development requires various efforts to balance the carrying capacity of the city's environment. Another environmental problem that also appears in urban areas, is traffic congestion which is at risk of increasing carbon monoxide emissions. Air pollution has both acute and chronic effects on human health, affecting a number of different organ systems. Ranging from mild such as upper respiratory irritation (ARI) for chronic respiratory and heart disease, to lung cancer, including acute respiratory infections in children and chronic bronchitis in adults, to pre-existing heart and lung diseases will aggravating the disease, or an asthma attack. This study analyzes the valuation of the degradation of air pollution in order to create a green city in Jakarta. The results of the Degradation Economic Valuation of the City of Jakarta are calculated from the number of pneumonia & tuberculosis patients multiplied by the cost of treatment per capita, the result is for the total DKI Jakarta in 2011 of Rp. 6,497,- (in million) while 2014 increased by Rp. 1,148,976,- (in million) while for 2020 it decreased by Rp. 98,535,- (in million). For 2020. This valuation represents the loss resulting from air pollution so that people have to pay for medical treatment due to illness suffered from pollutants